Optimalisasi Efek Chroma Key Pada Event E-Sport Live Streaming Menggunakan Color Correction - Argiyan Dwi Pritama; Irma Nur Cahyani (Jurnal Komputer Terapan, 2022)
Indonesian National Sports Committee (KONI) officially confess esports as one of competitive sports in Indonesia in 2020 for develop the potential to Digital Industry in the field of sports, especially Electronics Sport. In this regard, the competition in the esports industry is getting more passionate for industry players in this field to compete for the attention of Indonesian eport lovers by competing to hold interesting and quality esports events. PT Ampu Kreatif Studio which has an E-Sport subdivision as EO & Media will also compete in this industry. Furthermore, competition will be maximized on the live streaming visual display presented, therefore, in this study entitled Optimizing the Chroma Key Effect on Live Streaming E-Sport Events Using the Color Correction Method is expected to improve the quality of visual displays in the live streaming process of esport events by using the Color Correction Method. The goal of attracting large audiences and esport lovers is of course maximizing the Chroma Key Effect using the Color Correction Method which is applied at the esport event held to produce an attractive visual appearance.